2011
DOI: 10.1084/jem.20102516
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signals through PI-3 kinase pathway modulate Th17 cytokine production by CCR6+ human memory T cells

Abstract: PI-3K–mediated repression of FOXO1 and KLF2 promotes proinflammatory cytokine expression by lineage-committed human CCR6+ Th17/Th22 memory cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 73 publications
4
103
0
Order By: Relevance
“…RORC was higher in the CCR6 + subsets and lower in the CCR6 2 subsets, a pattern consistent with that in Teff cells (22). TBX21 showed higher expression in the CXCR3 + subsets and lower in the CXCR3 2 subsets, as has been reported (11,16).…”
Section: Gene Expression Profiling Identifies Five Major Subgroups Ofsupporting
confidence: 87%
“…RORC was higher in the CCR6 + subsets and lower in the CCR6 2 subsets, a pattern consistent with that in Teff cells (22). TBX21 showed higher expression in the CXCR3 + subsets and lower in the CXCR3 2 subsets, as has been reported (11,16).…”
Section: Gene Expression Profiling Identifies Five Major Subgroups Ofsupporting
confidence: 87%
“…In view of our results, Foxo1 can act as a repressor of RORgt, the master gene that unlocks the Th17 differentiation program. In human CCR6 + memory T cells, a similar mechanism might take place, as it has been recently reported that overexpression of FOXO1 decreases IL-17A (56). Activating Foxo1, with drugs acting either on pathways upstream this TF or directly controlling its activity, therefore offers a new means to control RORgt function and dampen Th17 responses.…”
Section: Pharmacological Modulation Of Foxo1 Activity Controls Th17 Dmentioning
confidence: 88%
“…The PI3K/AKT pathway has been associated with Th17 cell development (38) and with IL-17 expression by CCR6 + human memory T cells (39). Thus, targeting MAPK/ERK along with the JAK/ PI3K/AKT pathways may be beneficial for inhibiting Th17-mediated bone loss.…”
Section: Discussionmentioning
confidence: 99%